Pengaturan Renvoi Pada Minuta Akta Notaris - Permatasari, Dewa Ayu Putu Dian; I Dewa Ayu Dwi, Mayasari (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024)DO - 10.24843/AC.2024.v09.i01.p10, 2024)
The purpose of writing this article is to find out the regulations regarding repairs or renvoi in notarial deeds and to find out the legal consequences of repairing renvoi of notarial deeds that are not initialed by the parties. This writing uses a normative legal research method by examining the UUJN and the notary's code of ethics using a statutory approach, a conceptual approach and a systematic approach using primary legal materials such as related laws and regulations and secondary legal materials, namely legal opinion journals and the internet and other legal materials. The results of research on regulations regarding renvoi on notarial deeds are that there are 2 types of errors, namely errors that are substantial and errors that are not substantial. Renvoi on a deed is done by changing it, crossing it out, adding it, inserting it, but a change is considered valid if it also includes an initial. the parties to the renvoi, the parties include the witness notary and interested parties. The legal consequences if the renvoi is not initialed in the deed can be null and void or not have perfect evidentiary power, so that the deed is a private deed, that violation of the provisions regarding improvements in the deed results in a deed only having evidentiary power as a private deed and can be a reason for parties who suffer losses to demand reimbursement of costs, compensation and interest from the Notary